Restorasyon Alanında Koruma Laboratuvarının Önemi Ve Koruma Laboratuvar Çalışmalarının Örnek Bir Yapı Üzerinde Değerlendirilmesi - Çelik, Nihan Çetinbaş (Fen Bilimleri Enstitüsü, 2015)
Kültür mirası sayılan eserlerin malzemelerinin kompozisyonlarının belirlenmesi, koruma çalışmalarında verilecek kararlar açısından önemli bir bilgidir. Restorasyon uygulamaları sırasında kullanılan malzemelerin fiziksel özelliklerinin özgün malzemelere yakın olması gerekliliği günümüzde açık olarak bilinmektedir. Tarihi yapıların restorasyonları sırasında koruma amaçlı yapılacak olan analizler, bu yapıların bilimsel olarak tanınabilmesi için son derece gereklidir. Kimya, malzeme ve mimarlık disiplinlerinin ortak çalışmaları ile eserlerin koruma ve restorasyon çalışmaları daha sağlıklı yürütülmektedir.                               Bu çalışma restorasyon alanında koruma laboratuvarının yeri ve önemine değinirken, güncel kurum ve kuruluşları, kullanılan ekipman ve analizleri içermektedir. Örnek çalışma için belirlenen deney yöntemleri ile analizleri yapmak, malzemelerin özelliklerini belirlemek ve bu bilgiler ışığında onarım, temizlik önerilerinde bulunurken kimya alanı dışında ihtisasını yapan mimarlık ve restorasyon ile ilgili tüm bilim dallarında çalışmalarını sürdüren kişiler için bir kaynak oluşturulması hedeflenmiştir. Çalışmanın birinci bölümünde amaç ve yöntem üzerinde durulmuştur. İkinci bölümde literatür ve kaynak araştırması yapılarak restorasyon çalışmalarının tarihçesi, yurt dışındaki güncel kurum ve kuruluşlar ile fonksiyonları araştırılmıştır. Üçüncü bölümde ise ülkemizdeki kurum ve kuruluşlar ile yasal gereklilikler ve bilimsel zorunluluklar hakkında bilgiler derlenmiştir.  Tez çalışmasının dördüncü bölümünde yapılan çalışmalara örnek teşkil etmesi amacıyla Serkl Doryan yapısının tarihçesi araştırılmış, mevcut durumu analiz edilmiş ve yapıda karşılaşılan sorunlar fotoğraflarla detaylı olarak incelenmiştir. Daha sonra tespit edilen noktalardan ileri analiz işlemleri için örnek toplama aşamasına geçilmiştir. Örnekler yapının dokunulmamış ve tamir görmemiş kısımlarından ve çapraz karşılaştırma yapabilmek adına farklı katları ve cephelerinden alınmıştır. Bir murç ve çekiç yardımıyla yapılara zarar vermeden alınan örnekler ayrı ayrı torbalara yerleştirilmiş ve her birinin içine yapının adının, yerinin, örneğin yapının neresinden alındığının ayrıntılı tanımının ve bir örnek numarası içeren kartlar eklenmiştir. Tüm örnekler genel ve makro şekilde fotoğraf ile belgelenmiştir. Sonraki aşamada laboratuvarda örnekler analiz edilmiş bağlayıcı/agrega oranları, agrega boyut dağılımları ile görsel özellikleri tespit edilmiştir. Örneklerin nem, organik katkı/bağıl su ve CaCO3 yüzdeleri hesaplanmış, agregalar stereo-mikroskop altında gözlemlenmiştir. Suda çözünebilir tuz analizleri ve protein-yağ analizleri gerçekleştirilmiş ve örneklerin ince kesitleri detaylı analiz edilmiştir.  Analiz sonuçlarının ışığında yapıdaki malzemeler türlerine ve içeriklerine göre sınıflandırılmış, yapıda bulunan taş, harç, sıva, ahşap ve boyalar için onarım ve temizlik reçeteleri ile koruma önerilerine yer verilmiştir. Çalışmanın devamında bu öneriler ışığında gerçekleştirilen uygulamalardan örnekler gösterilmiştir. Beşinci bölümü oluşturan sonuç kısmında ise ülkemizde gerçekleştirilen restorasyon çalışmalarının bilimsel niteliği değerlendirilmiş ve geliştirilmesi gereken noktalar üzerinde durulmuştur.

Determination of the composition of cultural heritage materials is an important step in conservation. The necessity of using a similar or compatible material to the authentic one is known clearly by the professionals in restoration field. To analyze the historical materials and examine them scientifically is extremely important for the protection of the cultural heritage. These research studies must be held with the collobration of the fields chemistry, materials, architecture and restoration. This thesis document emphasizes the importance of the conservation laboratory in restoration field with a case study Cercle D’Orient building in Taksim, Istanbul. The aim and the methodology of the work were indicated in Chapter 1. The first aim of the project was to create a guide for the professionals in the conservation area who were interested in scientific search of the cultural heritage and multidisciplinary work. The second aim was to propose scientific conservation solutions for our case study building. For this a classic methodology was followed. After the literature search and getting information about the current state of the building, the problems were defined. Next step was material sampling as representative of each problem from different levels and facades. The analysis of the samples gave us the building’s material properties and intervention periods.   First part in Chapter 2 presents the milestones of the conservation laboratory in the restoration and conservation history. The second part of this chapter includes the main institutes, universities, laboratories and organizations in the Unites States of America and Europe serving for the restoration field.  Besides these there are also private companies ready to serve for the scientific research of the cultural heritage.  Chapter 3 consists the history of the restoration work, laboratories and universities working in the conservation field in Turkey. The first regulation regarding the conservation of cultural heritage ‘Asar-ı Atika Nizamnamesi’ was at 1874 with the final version at 1906. Today ‘Cultural and Natural Heritage Conservation Law’ numbered 2863 is the valid law which was first published at year 1983. İstanbul Restoration and Conservation Laboratory was the first public laboratory founded at 1984, still working on analysis and research of historical buildings, monumets and artwork. This chapter also consists a part including the current laws and their sections which are related with conservation of the cultural heritage. The items in the sections emphasizes the pre-analysis of the properties and using the authentic materials and methods during restoration work. The chapter continues with scientific necessities for the conservation methods. If the restoration work is held without any research and done by a common repair work recipe, the cultural property is convicted to the extra loads and fast attritions because of the usage of the incongruous materials. Besides many material conservation laboratories located in the architecture departments of the universities, there are also public laboratories located in 32 municipalities and 12 special provincial administrations in the cities of Turkey.  The case study-Cercle D’Orient building- was examined in detail in Chapter 4. The building is located in İstiklal Street Taksim, İstanbul. It was built in 1884 and its architect was Valluri. The architectural plan of the building was designed to serve as a club for foreigners living in Istanbul. After this function of the building, it was used as a cinema, theatre and a mall. The building was ruined because of several fire incidents. Nowadays Cercle D’Orient is under restoration to serve as a shopping mall in Grand Pera project. After the research of history of the building, the chapter continues with the current problems and damages. Both exterior and interior damages and their reasons were investigated in detail and presented with the photographs.  After that the problems were observed according to the classified building materials such as stone, plaster, mortars, wood and metal. The stone deteriorations were classified with the ‘Illustrated Glossary on Stone Deterioration Patterns’ guideline which was released by ICOMOS at 2008. They were also defined in detail with the support of the photographs taken at the construction site. In order to choose the right materials to apply during the restoration, the material analysis are done in Istanbul Technical University, Faculty of Architecture Conservation Laboratory as a revolving fund project.  The scientific tests are also presented in this chapter under the titles; sampling, visual analyses, binder/aggregate ratios, aggregate size distrubution and the visual properties of the aggregates, minerological, chemical and micro-structure, physical properties and mechnanical properties. The results of the characterization analyses presented that most of the samples are non-hydraulic lime mortars with sand aggregates and cement. The plasters are lime plasters with gypsum. The stones are 92% micritic lime stone called Malta stone. The binder/aggregate ratios of the samples were mainly 1/2, 2/3 and 1/3. The aggregate size distribution is compatible with the ideal curve. The deviations belong to the samples with finer aggregates, taken from roof level and gypsum added plasters.   The mechanical properties were low as expected considering that most of the samples were non-hydraulic lime mortars. The results were demonstrated by charts and diagrams and were intensively discussed in this chapter. Finally, the samples were grouped based on the characterization analyses. This part also includes other materials such as paints. It is observed that oilpaint and synthetic polymer paints are used on the walls. The wooden structures and decorations are examined by Doç. Dr. Papatya Seçkin from Mimar Sinan Fine Arts University. The research was followed by the conservation proposals. In this part cleaning, stone repair, reinforcement, mortar, plaster, paint and wood repairs are given as recipes for the implementation. The results were comprehensively presented in Chapter 4. The before and after photographs are used to see the first applications in the directions of given proposals. Chapter 5 includes the conclusion part with an overview of the thesis and some comments on the current situation of restoration principles in our country. The research showed that the experience and interdisciplinary collaboration is strongly needed for the conservation of cultural heritage. This is proved throughout the thesis with the examples of the institutions and organizations located at United States and Europe. The collaboration between restoration professionals and researchers working in this area is the keypoint for an healthy conservations project.  Analyzing the building materials in detail is very important to suggest the recipes for the production of compatible repair materials. The repair materials should be derived from the same region with the authentic samples in order to make a compatible restoration work. Scientific research on different kinds of materials such as wood, stone, mortar or plaster must be investigated by a researcher with this profession. The presence of a specialized chemist to work on the experiments of these type of materials is really important. To improve the properties of repair materials must be supported by institutions and industry. The work also indicates that a proper conservation can be achievable by interdisciplinary research with the participation of architects, chemists, art historians, material engineers, civil engineers and geology engineers. As the succesful projects become more visible, the societies cultural heritage perception will change in positive manner and the tangible and cultural value of the historical properties and piece of arts will grow.
Importance Of Conservation Laboratory In Restoration And Evaluation Of Conservation Laboratory Work On A Cultural Heritage Building As A Case Study
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: Restorasyon; konservasyon; mimari koruma; mimari koruma laboratuvarı; Restoration; conservation; architectural conservation; architectural conservation laboratory